Your money : the missing manual - Roth, J. D. (Missing manual., 2010)
"Get the info you need to make sensible decisions on saving, spending, and investing; learn the best ways to set--and achieve--financial goals; set up a realistic budget framework and learn how to track expenses; discover proven methods to help you eliminate debt; understand how to use credit wisely; win big by making smart decisions on your home and other big-ticket items; learn how to get the most from your investments by avoiding rash decisions; decide how--and how much--to save for your retirement"--Page 4 of cover.